PENINGKATAN INOVASI MELALUI KREATIFITAS INDIVIDU PANTI ASUHAN PUTRI HARAPAN IBU BANJARMASIN - Rahmi Widyanti; Mohammad Zainul; Ervica Zamilah (Universitas Islam kalimantan MAB, 2022)
One of the uses of natural resource wealth in the form of processed food, one of which is snacks or cakes. Pastries are traditional snacks made from flour and eggs and are quite popular in the community, especially on festive days. Cookies are made from flour and eggs, which are mixed with rice flour and other ingredients, and then baked. The snack industry business has become a regional snack food so that other cities are even favored by both young and old. This training activity aims to help the orphanage children or their caretakers in growing creative thoughts / ideas to produce other products so that they are able to find their own income without expecting continuous government assistance. It is hoped that this training can increase the innovation of the orphanage children. The problem faced by the orphanage is that after leaving the orphanage they do not have skills. Therefore, the environment demands creativity and innovation to open an independent business. Through this training, it can open the thinking horizons of the orphanage children and the caretakers of the orphanage to business opportunities.